General election and stock market performance: a Malaysian case / Faridah Najuna Misman, Shashazrina Roslan and Muhammad Izzat Mat Aladin - Misman, Faridah Najuna; Roslan, Shashazrina; Mat Aladin, Muhammad Izzat (UiTM Cawangan Johor, 2019)
The 2018 Malaysia general election has marked a new history for the Malaysia political structure. After more than 60 years Barisan Nasional ruling the country, in the 2018 general election Barisan Nasional lose the game to the Pakatan Harapan. The results of the 14th general election has caused a shock not only to political arena but also to the Malaysian financial market. Therefore, this paper aims to investigate if there is any significant effect of 14th Malaysia general election on the Malaysia financial market specifically the stock market. Results from the statistical analysis reveal that there are significant changes in the Malaysia stock market performance after the 14th general election.